Perception of family functioning: psychometric analysis of Family APGAR Scale in adolescents in Lima - Castilla, Humberto A. (2014)
The article describes the psychometric analysis of the APGAR Scale developed by Smilkstein (1978), consisting of five Likert items with five alternatives, which evaluates the perception of family functioning (Gómez & Ponce, 2010). The scale was administered to 256 male students aged from 11 to 18 attending state school in Lima. Item-test correlation analysis provided evidence of highly significant relations (p<0.001) for each of the reagents, indicating that reagents evaluate indicators of the same construct. To assess the perception of family functioning, APGAR Scale has moderate internal consistency (Cronbach a = .788). Construct validity was established by factor analysis and a single factor was obtained through a principal component analysis and the orthogonal rotation (Varimax).